Pengelolaan Website Desa Dalam Rangka Menunjang Informasi Berbasis Digitalisasi Pada Masyarakat Di Desa Palae, Kecamatan Sinjai Selatan - Abd. Wahid (Universitas Mbojo Bima, 2024)
This study aims to determine Village Website Management in the Context of Supporting Digitalization-Based Information for Communities in Palae Village, South Sinjai District. This study uses qualitative research methods, namely data collection using direct observation techniques, interviews, and documentation. The data analysis techniques used by the authors are data reduction, data presentation and conclusion. Data collection was carried out through observation, interviews and documentation. The data obtained were analyzed based on the indicators determined by looking at the results of observations, interviews and documentation from research informants. The informants used were the Village Government, Website admin, and the Palae Village Community. Based on the results of research on website management Village Website Management in the Context of Supporting Digitalization-Based Information for Communities in Palae Village, South Sinjai District, it can be concluded in general that the management of the website after being traced is not good enough. Judging from several indicators, namely: timeliness, completeness, reliability, accuracy, there are several weaknesses or deficiencies, namely some important data and information about Palae Village are not yet available on the website, some menus and the sub menu is not functioning properly and the website is not useful enough for the public. As well as handling errors that have not been maximized.